2005
DOI: 10.1186/1471-2458-5-124
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular health knowledge and behavior in patient attendants at four tertiary care hospitals in Pakistan – a cause for concern

Abstract: BackgroundKnowledge about coronary heart disease (CHD) and its risk factors is an important pre-requisite for an individual to implement behavioral changes leading towards CHD prevention. There is scant data on the status of knowledge about CHD in the general population of Pakistan. The objective of this study was to assess knowledge of CHD in a broad Pakistani population and identify the factors associated with knowledge.MethodsCross sectional study was carried out at four tertiary care hospitals in Pakistan … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

36
92
7
5

Year Published

2009
2009
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 78 publications
(140 citation statements)
references
References 12 publications
36
92
7
5
Order By: Relevance
“…Results showed that those with less than high school education and with an annual income of less than $50,000 CAD had significantly lower CHD knowledge. This is consistent with what has been reported in the literature [7,17,19,23,26,29], whereby those with advanced education and income were more knowledgeable about CHD. These findings are problematic because low SES is strongly associated with an increased prevalence of CHD risk factors [4,53,54] and with greater morbidity and mortality among CHD patients [48,49,55,56].…”
Section: 12supporting
confidence: 82%
See 3 more Smart Citations
“…Results showed that those with less than high school education and with an annual income of less than $50,000 CAD had significantly lower CHD knowledge. This is consistent with what has been reported in the literature [7,17,19,23,26,29], whereby those with advanced education and income were more knowledgeable about CHD. These findings are problematic because low SES is strongly associated with an increased prevalence of CHD risk factors [4,53,54] and with greater morbidity and mortality among CHD patients [48,49,55,56].…”
Section: 12supporting
confidence: 82%
“…As well, contrary to previous studies which found that South Asians are significantly lacking in CHD knowledge [17,29,50], we were unable to find a difference between South Asians and non-South Asians. The lack of a significant effect may have been due to insufficient power considering the small number of South Asian patients in this study, or due to the fact that other studies examined South Asians alone and did not make comparisons to other ethnic groups.…”
Section: 12contrasting
confidence: 56%
See 2 more Smart Citations
“…En una investigación realizada en Pakistán los individuos estudiados identificaron como factores de riesgo al estrés, HTA, sobrepeso y sedentarismo (26), mientras que en el presente trabajo los factores identificados con mayor frecuencia fueron la grasa dietaria y el hábito tabáquico, en semejanza a lo reportado en Canadá y en otro estudio paquistaní (6,24). Dicho patrón de conocimiento pudiera deberse a que las campañas de prevención para ECV profundizan en la erradicación del hábito tabáquico y en la disminución del consumo de grasas saturadas.…”
Section: Discussionunclassified